Comparative Study of Bullying Victimization Among Students in General and Special Education. (January 2015) - Hartley, Michael T.; Bauman, Sheri; Nixon, Charisse L.; Davis, Stan
Research on bullying is an important avenue for understanding the social integration of students in special education. Focused on 3, 305 students who self-reported victimization of two to three times per month or more, this study compared the pattern of verbal, relational, and physical bullying among students in general education and special education. Overall, students in special education reported more physical and emotional harm as well as more psychological distress as a result of their victimization. Self-reported rates of verbal and relational victimization were similar, but physical victimization was more often reported among students in special education. In addition, adult teachers and staff were more likely to verbally, relationally, and physically bully students in special education, according to student self-report.